Electrical characterization and conduction mechanism study of multi-functional thin films for electronic devices - Adi Saat Mohamed Osman (2015)
Over the years, a growing interest has been made regarding the usage of magnetoelectric multiferroic in relation to the field of memory devices due to the magnetoelectric effect in contrast to traditional materials. This project will investigate the properties of a magnetoelectric multiferroic material, Pb(Zr,Ti)O3-Pb(Fe,Ta)O3 (PZTFT). Thin films of PZTFT were fabricated using a pulsed laser deposition (PLD) technique. To analyse the quality of the thin films fabricated, processes such as X-ray diffraction (XRD) technique, Atomic Force Microscopy (AFM) and Reflection High-Energy Diffraction were used. Based on the experiment done, it is found that a number of parameters will affect the surface smoothness of the thin film during the growth of PZTFT. After the preparation of PZTFT thin films, its conduction mechanism and ferroelectric properties were investigated under the different conditions. Different conduction mechanism were investigated in response to an applied electric field and a polarization hysteresis loop were measured. The leakage current and remnant polarization of the PZTFT samples were below expectations according the experimental data.